Reimagining Islamic Legal Education: Toward a Holistic Framework for Syariah and Legal Studies - Raveenthiran Vivekanantharasa; Rusdiana Priatna Wijaya; Yashar Mammadov (Journal of Islamic Law and Legal Studies, 2026)
This study explores the development of a sustainable framework for Syariah and legal studies within the context of contemporary educational transformation. Employing a qualitative research approach through content analysis, this study examines relevant scholarly literature, Islamic legal sources, and contemporary educational perspectives to identify key strategies for strengthening Syariah and legal education in response to evolving societal challenges. The findings reveal that the sustainability of Syariah and legal studies requires an integrated approach that combines classical Islamic scholarship with modern legal, social, and technological developments. Several essential dimensions are identified, including institutional reform, curriculum innovation, pedagogical transformation, research advancement, international academic collaboration, and technology integration. Furthermore, the study highlights the importance of interdisciplinary engagement between Syariah studies and other fields, such as constitutional law, international law, economics, sociology, and digital studies. The findings also emphasize the significance of student-centered learning, critical thinking, and research-based education in enhancing academic quality and intellectual engagement